Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Konsumen Bandung Cheesecuit di Store Jatiwaringin - Dina Sabila (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Consumer purchasing decisions for dessert products are increasingly effected by various marketing aspects, particularly price also product quality, requiring business to understand this factors to improve competitiveness. This study aims to examine the extent to which price and product quality influence consumer purchasing decisions at Bandung Cheesecuit Jatiwaringin store. This research employed a quantitative approach with data collected using a Likert-scale questionnaire. The sample consisted of 100 respondents selected using purposive sampling also analyzed using SPSS 27. The result reveal that both price also things quality have a positive and significant effect on buying decisions, either partially or simultaneously. This is evidenced by the t-value of price (4,836) and product quality (4,877), both exceeding the t-table value of 1,985, and also the F-value of 66,804 > than the F-table value of 3,09 with a significance of 0,000 < 0,05. This findings suggest that the more appropriate the price and the better the perceived product quality, the higher consumers purchasing decisions. Therefore, companies should maintain competitive pricing and continuously improve things quality in order to strengthen consumer purchasing decisions.